Evaluation of muscle fatigue during 100-m front crawl - Stirn, I.; Jarm, T.; Kapus, V.; Strojnik, V. (European Journal of Applied Physiology, 2011)
The aim of this study was to evaluate muscle fatigue in upper body muscles during 100-m all-out front crawl. Surface electromyogram (EMG) was collected from the pectoralis major, latissimus dorsi and triceps brachii muscles of 11 experienced swimmers. Blood lactate concentration level increased to 14.1 ± 2.9 mmol l-1 5 min after the swim. The velocity, stroke length and stroke rate calculated based on video analysis decreased by 15.0, 5.8 and 7.4%, respectively, during the swim. EMG amplitude of the triceps and the lower part of the latissimus muscles increased, whilst the mean power frequency (MNF) of all muscles significantly decreased by 20-25%. No significant differences in the relative MNF decrease were observed amongst the muscles; however, the differences in the rate of the MNF decrease between the lower part of the latissimus and the triceps brachii muscles were found (P\0.05). The time of rest between the muscle activation of the two consecutive arm strokes at the end of swimming was extended (P\0.05). It was concluded that 100-m all-out crawl induced significant fatigue with no evident differences amongst the analysed muscles.